Perspectives on the ancient Maya of Chetumal Bay (Maya studies, 2017)
The ancient Maya invested massive amounts of labor on road systems (sacbeob) for communication and trade, yet Chetumal Bay, situated between modern day Quintana Roo, Mexico, and Corozal District, Belize, provided an economical alternative: an extensive network of riverine and maritime waterways to journey to the edges of Mayab and beyond. This volume reports recent work at sites important to Maya archaeology in the region that depended on waterborne exchange for their livelihood, including Cerro Maya (Cerros), Oxtankah, and Santa Rita Corozal.